2000
DOI: 10.1002/1531-8249(200005)47:5<670::aid-ana20>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mutation type and X chromosome inactivation on Rett syndrome phenotypes

Abstract: We screened 71 sporadic and 7 familial Rett syndrome (RTT) patients for MECP2 mutations by direct sequencing and determined the pattern of X chromosome inactivation (XCI) in 39 RTT patients. We identified 23 different disease-causing MECP2 mutations in 54 of 71 (76%) sporadic patients and in 2 of 7 (29%) familial cases. We compared electrophysiological findings, cerebrospinal fluid neurochemistry, and 13 clinical characteristics between patients carrying missense mutations and those carrying truncating mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
112
3
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(126 citation statements)
references
References 16 publications
10
112
3
1
Order By: Relevance
“…Three studies have found weak but inconsistent associations. Amir et al (2000) found that respiratory dysfunction was more common in patients with truncating mutations than in patients with missense mutations, but that the latter had higher levels of CSF HVA. Scoliosis was also more common in patients with missense than truncating mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies have found weak but inconsistent associations. Amir et al (2000) found that respiratory dysfunction was more common in patients with truncating mutations than in patients with missense mutations, but that the latter had higher levels of CSF HVA. Scoliosis was also more common in patients with missense than truncating mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Is it possible that some part of the function of MECP2 may be preserved while another part is disabled? Present evidence suggests that an early (truncating) mutation may indeed prove more damaging than a late one (Amir et al, 2000); however, some geneticists, including those working on the mouse model, have suggested that any MECP2 mutation will obliterate its action altogether.…”
Section: Why Do Mecp2 Mutations Occur?mentioning
confidence: 96%
“…23 Moreover, and likely most important, the type and location of the mutations are known to modulate clinical severity. [23][24][25][26][27][28][29][30][31][32][33][34] In addition, since the time of the discovery of the MeCP2 mutation as a cause of the disease, the geneticists have learned that mutations in MeCP2 do not always correspond with RTT. 35 In fact, besides RTT, mutations in MeCP2 have also been identified in individuals who do not show the clinical features of RTT (e.g., asymptomatic female carriers, boys with MeCP2 mutations known to cause typical RTT in girls, and rare individuals with mutations in MeCP2 who present with other neurodevelopmental conditions), collectively termed as MeCP2-pathies.…”
mentioning
confidence: 99%